Neuroprotective Properties of Dimethyl Fumarate Measured by Optical Coherence Tomography in Non-inflammatory Animal Models - Dietrich, Michael; Hecker, Christina; Nasiri, Milad; Samsam, Sogol; Issberner, Andrea; Kohne, Zippora; Hartung, Hans-Peter; Albrecht, Philipp (Frontiers in Neurology, 2021)
While great advances have been made in the immunomodulatory treatment of multiple sclerosis (MS), there is still an unmet need for drugs with neuroprotective potential. Dimethyl fumarate (DMF) has been suggested to exert both immunomodulatory and neuroprotective effects in MS. To investigate if DMF has neuroprotective effects independent of immunomodulation we evaluated its effects in the non-inflammatory animal models of light-induced photoreceptor loss and optic nerve crush. This might also reveal applications for DMF besides MS, such as age related macular degeneration. Retinal neurodegeneration was longitudinally assessed by in vivo retinal imaging using optical coherence tomography (OCT), and glutathione (GSH) measurements as well as histological investigations were performed to clarify the mode of action. For light-induced photoreceptor loss, one eye of C57BL/6J mice was irradiated with a LED cold light lamp while for optic nerve crush the optic nerve was clamped behind the eye bulb. The other eye served as control. GSH was measured in the optic nerve, choroid and retina and immunohistological staining of retinal microglia (Iba1) was performed. Mice were treated with 15 or 30 mg DMF/kg bodyweight or vehicle. While no protective effects were observed in optic nerve crush, in the light-induced retinal degeneration model DMF treatment significantly reduced retinal degeneration. In these mice, GSH levels in the retina and surrounding choroid were increased and histological investigations revealed less microglial activation in the outer retinal layers, suggesting both antioxidant and anti-inflammatory effects.